Current Problems of International Legal Copyright Protection - L. V. Shvarts; S. M. Burova (Теоретическая и прикладная юриспруденция)
The article examines the level of international copyright protection from the perspective of such aspects as the urgent nature of copyright protection and the possibility of applying the institution of compulsory license. To this end, the norms aimed at protecting copyright holders in the Russian Federation, the CIS, the European Union and other foreign countries, in particular, in the USA, are analyzed. The most important international conventions in the field of copyright and related rights protection are reflected. The legal basis of the activity of courts in cross-border copyright relations is shown. The actual problems of private international law on the improvement of substantive and conflictof- laws legal regulation in this area are identified. The analysis suggests that the establishment of common criteria for calculating the term of copyright protection in a single unified act is due to the need to combine private and public interests in using the results of intellectual activity and their exceptional importance for the globalization of the world economic and cultural space. Arguments about the possible introduction of compulsory licenses for copyrighted products of foreign companies, by analogy with those already provided for in Article 1362 of the Civil Code of the Russian Federation for objects of patent law, lead the authors to the conclusion that the mechanism of compulsory license should not take a permanent place in the regulation of intellectual property, since it will not significantly help in reducing economic risks and losses.